Indium tin oxide random network interconnection in dye sensitized solar cells - Shimon. (2009)
This project is aimed to provide comprehensive investigation on the photovoltaic energy conversion efficiency improvement by incorporating random network of interconnecting Indium Tin Oxide (ITO) structure in Titanium Dioxide (TiO2) based dye-sensitized solar cells (DSSC). This method requires shorter time, easier process and cheaper cost than other existing conductive path enhancement fabrication methods for DSSC.